The Influence of the Historical-Colonial Narrative on Trade Relations and Diplomacy Between Mexico and Spain (2015–2024) - Saenz Reyes, Blanca; Cruz Cruz, Mario; Sanchez Torres, Yolanda; Manzo Martínez, Lizet (Commercium plus, 2025)
This research analyzes the political tensions in the Mexico-Spain bilateral relationship, which, rooted in a deep historical and social fabric, were accentuated by antagonistic discourse during the 2018–2024 administration. The main objective of the study is to assess the influence of this historical-cultural narrative as a diplomatic and commercial variable, with respect to stability and economic growth during that period. Theoretically, the research is based on an approach that conceives the historical-social context not as a mere background, but as an active diplomatic agent, possessing agency and, therefore, influencing the bilateral relationship. To achieve this, a mixed methodology is employed, combining a qualitative review of concepts with a quantitative and comparative analysis of trade and investment data during the administrations of Enrique Peña Nieto (EPN) and Andrés Manuel López Obrador (AMLO). Through Grubel-Lloyd analysis, the results indicate that the relationship was integrated into key sectors, demonstrating that, despite political differences, the economic dimension remains fundamentally relevant for both countries. Among the most significant findings, the analysis shows that, contrary to the initial hypothesis, the economic relationship not only demonstrated remarkable resilience but also strengthened.